Scooby-Doo! Mystery Incorporated. The complete season 2 [videorecording (DVD)] - Cook, Victor (Storyboard artist); Geda, Curt (Warner Bros. Entertainment, 2014)
Scooby-Doo and the Mystery Incorporated gang travel to Crystal Cove, a haunted town, to solve some of the local mysteries.